EXTRACTION, PHYSICOCHEMICAL, AND STRUCTURAL CHARACTERIZATION OF NANOCELLULOSE FROM PINEAPPLE (Ananas comosus) PEELS WITHPOTENTIAL FOR SUSTAINABLE PAPER APPLICATIONS (FULafia Journal of Science and Technology, 2026)
The heavy reliance on wood-based pulp for paper production accelerates significant loss of biodiversity, deforestation, and increased greenhouse gas emissions, highlighting the urgent need for sustainable non-wood alternatives. In this study, nanocellulose was extracted from pineapple (Ananas comosus) peels, an abundant and underutilized agro-industrial waste, and comprehensively characterized to evaluate its physicochemical and structural properties. Cellulose was isolated from powdered pineapple peels through sequential alkaline delignification and bleaching, followed by acid hydrolysis to obtain nanocellulose. The resulting nanocellulose was characterized by Fourier-Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD), while key hydration-related parameters were measured. A cellulose-based nanocellulose yield of 7.5 % was obtained, corresponding to a biomass-based yield of 12.9 %, with a bulk density of 0.55 g/mL and a water retention capacity of 0.25 g/g. FTIR spectra confirmed effective removal of lignin and hemicellulose, SEM revealed nanoscale fibrillar morphology, and XRD showed an increase in crystallinity index from 67.09 % (bleached cellulose) to 69.40 % in nanocellulose, indicating an enhanced structural order. Overall, the findings demonstrate that pineapple peel-derived nanocellulose exhibits desirable physicochemical and morphological characteristics suitable for sustainable paper applications. The observed structural features and hydration behavior suggest that pineapple peel-derived nanocellulose has characteristics that may be favorable for cellulose-based material development, supporting its potential use in sustainable paper-related applications.